2010
DOI: 10.1007/s00464-010-1033-y
|View full text |Cite
|
Sign up to set email alerts
|

Does precut technique improve selective bile duct cannulation or increase post-ERCP pancreatitis rate? A meta-analysis of randomized controlled trials

Abstract: This meta-analysis shows that the precut technique does not increase the primary cannulation rate. However, the technique reduces the risk of post-ERCP pancreatitis compared with conventional technique. Further large, well-performed, randomized controlled studies are needed to confirm these findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
41
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(41 citation statements)
references
References 23 publications
0
41
0
Order By: Relevance
“…It has been suggested, that precut sphincterotomy should be used early enough in a difficult cannulation to avoid numerous cannulation attempts and unnecessary injury to the papilla or to the pancreatic duct. Early use of precut sphincterotomy may reduce the risk of pancreatitis (24,25). The second cannulation attempt a few days after precut is usually easier (13,19,20).…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested, that precut sphincterotomy should be used early enough in a difficult cannulation to avoid numerous cannulation attempts and unnecessary injury to the papilla or to the pancreatic duct. Early use of precut sphincterotomy may reduce the risk of pancreatitis (24,25). The second cannulation attempt a few days after precut is usually easier (13,19,20).…”
Section: Discussionmentioning
confidence: 99%
“…5,7 There are studies suggesting that early institution of the precut is a safe and effective strategy even though conflicting results concerning post-ERCP adverse events have been reported when compared with conventional techniques. 8 However, these studies have seldomly addressed the impact of the precut timing in the global ERCP duration.…”
mentioning
confidence: 99%
“…51,[86][87][88][89][90][91] Meta-analyses support early precut when compared to ongoing cannulation attempts. [92][93][94] Definition of "early" and the precut technique are other variables. Lee et al 95 reported results using a sequential approach that involved "early" precut.…”
Section: Procedures Techniquesmentioning
confidence: 99%